The picture dictation activity for EFL in Primary Education: an experience with preservice teachers - Castillo-Rodríguez, Cristina Milagrosa; Navas-Romero, Cristina (National University of Singapore, 2023)
Teaching listening in a foreign language requires time, practice, and effort. The Picture Dictation is presented as a creative activity in which a teacher describes an illustration to their students who have to draw it afterwards. This paper aims at exploring the impressions of preservice teachers of Primary Education towards the implementation of a Picture Dictation as an activity for enhancing listening skills in young students. A total sample of 423 undergraduate students from two academic years were invited to participate. Out of this total, 233 participants (G1) implemented the activity in the virtual modality during 2020/2021 academic year, whereas 190 students (G2) applied the activity in the face-to-face mode in 2021/2022. Each participant completed an online survey, which was uploaded onto Moodle platform. The main results showed that G1 would have preferred to apply the activity in a classroom environment, while G2 found some difficulty in the timing of the activity. However, the advantages were focused on promoting creativity and fostering listening comprehension. Even though the implementation of this kind of activity to practise EFL is not new, our findings contribute to gathering the main perceptions and beliefs held by preservice teachers, as well as the future implementation for their professional practice.
https://e-flt.nus.edu.sg/about-e-flt/ "This is an open-access journal, which means that all content is freely available without charge to the use of his/her institution. Users are allowed to read, download, copy, distribute, print, search or link to the full texts of the articles, or use them for any other lawful purpose, without asking for prior permission from the publisher or the author."
Keywords: Lengua inglesa - Estudio y enseñanza; Investigación activa en educación; Enseñanza primaria; English as a foreign language; Pre-service teacher; Picture dictation; Primary education